Low-Energy High-Current Pulsed Electron Beam Surface Treatment on the Tribological Behavior of 17-4PH Steel Produced via Binder Jetting - Lorenza Fabiocchi; Marco Mariani; Andrea Lucchini Huspek; Matteo Pozzi; Massimiliano Bestetti; Nora Lecis (Lubricants)
Stainless steel 17-4PH is valued for its high strength and corrosion resistance but poses machining challenges due to rapid tool wear. This research investigates the use of pulsed electron beam surface treatment to enhance the surface properties of components fabricated by binder jetting additive manufacturing. The aim is to improve the tribological performance compared to the as-sintered condition and the H900 aging process, which optimizes hardness and wear resistance. Printed samples were sintered in a reducing atmosphere and superficially treated with an electron beam by varying the voltage and the pulse count. Results showed that the voltage affects the roughness and thickness of the treated layer, while the number of pulses influences the hardening of the microstructure and, consequently, the wear resistance. A reciprocating linear pin-on-disk wear test was conducted at 2 N and 10 Hz. Surface-treated samples exhibited lower coefficients of friction, though the values approached those of aged samples after the abrasion of the melted layer, indicating a deeper heat-affected zone formation. Still, the friction remained lower than that of as-printed specimens. This study demonstrates that optimizing electron beam parameters is vital for achieving surface performance comparable to bulk aging treatments, with significant implications for long-term wear resistance.